Exploring Community Survival Practices During The Covid-19 Pandemic Through Documentary Filmmaking Insights From Research on The Slopes of Mount Merapi - Rizkya Annissa Farhani; Rocky Prasetyo Jati (Universitas Sebelas Maret, 2021)
Documentary films are new strategies to deal with the types of data needed by researchers and analysts. Documentary films have also proven to be a methodologically in-depth research approach. This study aims to determine how production management makes